Novel nucleocytoplasmic protein O-fucosylation by SPINDLY regulates diverse developmental processes in plants. (June 2021) - Sun, Tai-ping
Graphical abstract: Highlights: SPINDLY (SPY) is a unique nucleocytoplasmic-localized protein O -fucosyltransferase (POFUT). The sequence and predicted 3D structure of SPY are similar to the TPR domain-containing OGTs, but are distinct from ER-localized POFUTs. O -fucosylation by SPY can regulate nuclear transcription factors/regulators by affecting protein stability or protein-protein interactions. SPY regulates many developmental processes and responses to biotic and abiotic stresses in plants. SPY-like genes are conserved in diverse organisms, except in fungi and metazoans. Abstract : In metazoans, protein O -fucosylation of Ser/Thr residues was only found in secreted or cell surface proteins, and this post-translational modification is catalyzed by ER-localized protein O -fucosyltransferases (POFUTs) in the GT65 family. Recently, a novel nucleocytoplasmic POFUT, SPINDLY (SPY), was identified in the reference plant Arabidopsis thaliana to modify nuclear transcription regulators DELLAs, revealing a new regulatory mechanism for gene expression. The paralog of AtSPY, SECRET AGENT (SEC), is an O -link- N -acetylglucosamine (GlcNAc) transferase (OGT), which O -GlcNAcylates Ser/Thr residues of target proteins. Both AtSPY and AtSEC are tetratricopeptide repeat-domain-containing glycosyltransferases in the GT41 family. The discovery that AtSPY is a POFUT clarified decades of miss-classification of AtSPY as an OGT. SPY and SEC play pleiotropic roles in plant development, and the interactions between SPY and SEC are complex. SPY-like genes are conserved in diverse organisms, except in fungi and metazoans, suggesting that O -fucosylation is a common mechanism in modulating intracellular protein functions.